Emergencies in public law : the legal politics of containment - Loevy, Karin (Cambridge University Press, 2016)
"Debates about emergency powers traditionally focus on whether law can or should constrain officials in emergencies. Emergencies in Public Law moves beyond this narrow lens, focusing instead on how law structures the response to emergencies and what kind of legal and political dynamics this relation gives rise to. Drawing on empirical studies from a variety of emergencies, institutional actors, and jurisdictional scales (terrorist threats, natural disasters, economic crises, and more), this book provides a framework for understanding emergencies as long-term processes rather than ad hoc events, and as opportunities for legal and institutional productivity rather than occasions for the suspension of law and the centralization of response powers"--